Arctic Environmental Test of Fuel Filter/Separators and Collapsible Petroleum Storage Reservoirs - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1969)
The objective of the procedures is to provide a means of evaluating the performance of fuel/separators and collapsible storage reservoirs under arctic winter environmental conditions.